Networking our science to characterize the state, vulnerabilities, and management opportunities of soil organic matter. (5th October 2017) - Harden, Jennifer W.; Hugelius, Gustaf; Ahlström, Anders; Blankinship, Joseph C.; Bond‐Lamberty, Ben; Lawrence, Corey R.; Loisel, Julie; Malhotra, Avni; Jackson, Robert B.; Ogle, Stephen; Phillips, Claire; Ryals, Rebecca; et al.
Abstract: Soil organic matter (SOM) supports the Earth's ability to sustain terrestrial ecosystems, provide food and fiber, and retains the largest pool of actively cycling carbon. Over 75% of the soil organic carbon (SOC) in the top meter of soil is directly affected by human land use. Large land areas have lost SOC as a result of land use practices, yet there are compensatory opportunities to enhance productivity and SOC storage in degraded lands through improved management practices. Large areas with and without intentional management are also being subjected to rapid changes in climate, making many SOC stocks vulnerable to losses by decomposition or disturbance. In order to quantify potential SOC losses or sequestration at field, regional, and global scales, measurements for detecting changes in SOC are needed. Such measurements and soil‐management best practices should be based on well established and emerging scientific understanding of processes of C stabilization and destabilization over various timescales, soil types, and spatial scales. As newly engaged members of the International Soil Carbon Network, we have identified gaps in data, modeling, and communication that underscore the need for an open, shared network to frame and guide the study of SOM and SOC and their management for sustained production and climate regulation.